IMPLEMENTASI MODEL THINK PAIR SHARE (TPS) MELALUI DISKUSI KELOMPOK KECIL DALAM PEMBELAJARAN IPAS KELAS V DI SD NEGERI 2 BUNUTIN - Wina Adnyani, Ni Wayan; Arini, Ni Wayan; Ayu Suciartini, Ni Nyoman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is a process of developing students’ potential holistically, covering spiritual, cognitive, affective, and psychomotor aspects. In science learning, students are expected to actively understand natural and social phenomena; however, learning practices at SD Negeri 2 Bunutin were still predominantly teacher-centered, resulting in low student participation in discussions, limited confidence in expressing opinions, and less optimal independent thinking skills. This study aimed to describe the implementation of the Think Pair Share (TPS) model through small-group discussions in fifth-grade science learning at SD Negeri 2 Bunutin. This research employed a qualitative descriptive approach involving the fifth-grade homeroom teacher, fifth-grade students, and the school principal as research subjects. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The TPS model was implemented through several stages, including introductory activities, core learning activities, the think, pair, and share stages, and closing activities. The findings revealed that at the think stage students were given opportunities to think independently about the material or problems presented by the teacher. At the pair stage, students worked in small groups to exchange ideas and deepen their understanding, while at the share stage they presented discussion results to the class, fostering interaction and idea-sharing among peers. The implementation of the TPS model positively impacted student participation, collaboration, confidence in expressing opinions, and understanding of science concepts, although challenges such as limited instructional time and classroom conditions were still encountered during its implementation.